PEMOLESAN TUMPATAN KOMPOSIT DAPAT MENURUNKAN ANGKA PERUBAHAN WARNA (DISKOLORISASI) PADA RESIN KOMPOSIT NANOFILLER YANG DISEBABKAN OLEH PENGGUNAAN OBAT KUMUR CHLORHEXIDINE - I Gusti Ketut Armiati (Faculty of Dentistry, Mahasaraswati Denpasar University, 2019)
Nanofiller composite resin restoration has a major problem, namely color changes. Polishing are factors that determine color change and if added to using mouthwash for a long time can cause more significant color changes. The 0.2% chlorhexidine gluconate mouthwash is a mouthwash that is often used in the community because it has low toxicity. However, using the chlorhexidine gluconate 0.2% mouthwash in the long term can cause discoloration in the composite resin. The purpose of this study was to determine the difference between discoloration of polished and unpolished nanofiller composite resin on the soaking of 0.2% chlorhexidine gluconate mouthwash. The method used in this study is purely experimental research with a pretest and post test with control group design, using 24 samples of premolar teeth prepared with class II cavity design and then filled with nanofiller composite resin. The samples were then divided into 4 treatment groups, namely polished, non-polished nanofiller composite resin, 0.2% chlorhexidine gluconate mouthwash and distilled water. Soaking was carried out 24 hours a day for 5 days in an incubator at 37ºC. Changes in the color of each group were measured using Shade Guide Vita Classical. The hypothesis testing of this research was carried out by descriptive analysis which was then tested by the Shapiro-Wilk test for its normality test and Leven's test to test its homogeneity with a significance value of 0.05. Mann-Whitney test for different tests. Based on the results of this study, it was found that the discoloration of the polished nanofiller composite resin was smaller than that which was not polished on the soaking of chlorhexidine mouthwash 0.2%